Nutritional status and bacteremia patterns in children with diarrheal diseases: A comparative analysis of bacteremia from Salmonella Typhi versus other pathogens - Md Rezaul Hossain; Monira Sarmin; Irin Parvin; Mst Mahmuda Ackhter; Afsan Bulbul; Chidozie Declan Iwu; Mohammod Jobayer Chisti; Lubaba Shahrin (PLoS ONE, 2025)
Background Bacteremia remains a significant concern among under-five children with diarrheal diseases, particularly in resource-limited settings. Distribution of bacteremia patterns across the patient’s nutritional status and outcomes have never been analyzed. This study aimed to investigate the association between nutritional status and bloodstream infections caused by Salmonella enterica serovar Typhi compared to other pathogenic bacteria in children with diarrheal diseases. Methods A retrospective case-control study was conducted using electronic medical records from icddr,b (Dhaka, Bangladesh) between 2019−20. Cases were defined as children (< 60 months) hospitalized with diarrheal disease and diagnosed with Salmonella Typhi bacteremia; controls included children with bloodstream infections caused by other than typhoidal bacteria, including Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Streptococcus spp. Nutritional status was categorized as well-nourished, Moderate Acute Malnutrition (MAM), or Severe Acute Malnutrition (SAM). Descriptive statistics and multiple logistic regression models were used to assess associations between nutritional status, bacteremia type, and clinical outcomes. Results Among 162 children with confirmed bloodstream infections, 74 (45.68%) had Salmonella Typhi bacteremia, while 88 (54.32%) had bacteremia caused by other bacterial isolates. SAM was more prevalent among children with other bacteremia (78.12%) than caused by Salmonella Typhi. Conversely, well- nourished children were more likely to develop Salmonella Typhi bacteremia (66.13%) compared to MAM (32.61%) and SAM (21.88%) cases. After adjusting for comorbidities and prior antibiotics use, logistic regression analysis found malnourished children had significantly lower odds of developing Salmonella Typhi bacteremia compared to well-nourished children (SAM: aOR 0.157, 95% CI: 0.045–0.548, p = 0.004; MAM: aOR 0.238, 95% CI: 0.089–0.640, p = 0.004). Mortality rates were significantly higher among controls (11.73%) compared to Salmonella Typhi cases (1.35%), particularly for infections caused by Klebsiella pneumoniae (66.67%) and E. coli (31.25%). Conclusion Malnourished children are at higher risk for severe bloodstream infections caused by other bacterial species, leading to higher mortality rates and increased antimicrobial resistance. However, Salmonella Typhi bacteremia occurred more frequently in well-nourished children. These sort of distribution of bacteremia patterns across patients’ nutritional status can provide insights and improve clinical management.